Markets, Distribution, and Exchange After Societal Cataclysm - Rayner, S; Cantor, R; Stuart, H (Books for Business, 2000)
This report identifies constraints and opportunities for the restoration of economic exchange after nuclear war. Four survival scenarios are postulated based on high or low levels of damage to (1) institutions that signal trading opportunities, reduce transaction costs, and regulate and enforce contracts, and (2) resources that are used to create and define wealth. The four scenarios are Best case, Worst Case, Resource Abundance, and an Institution Intensive case. Discussed in depth are such items as property rights, barter, currency, trust, credit, supply and demand, and trust as related to authority.